Gender Dysphoria and Its Non-Surgical and Surgical Treatments - Danyon Anderson; Himasa Wijetunge; Peyton Moore; Daniel Provenzano; Nathan Li; Jamal Hasoon; Omar Viswanath; Alan D. Kaye; Ivan Urits (Health Psychology Research)
Gender dysphoria is defined by severe or persistent distress associated with an incongruence between one's gender identity and biological sex. It is estimated that 1.4 million Americans and 25 million people worldwide identify as transgender and that 0.6% of Americans experience gender dysphoria. The pathophysiology of gender dysphoria is multifactorial and incompletely understood. Genetics, androgen exposure, neuroanatomy, brain connectivity, history of trauma, parents with psychological disorders, and being raised by less than two parents are associated with gender dysphoria. Gender dysphoria most frequently presents in early teenage years but can present earlier or later. Anxiety and depression are the two most common comorbid diagnoses and may be the reason for presentation to medical care. Diagnosis is established through history and or validated questionnaires. Treatment includes psychosocial therapy, pharmacotherapy for underlying depression and/or anxiety, hormonal therapy, non-genital and/or genital feminization or masculinization operations. The frequency and severity of treatment related morbidity increases progressively as treatments go from conservative to more invasive. Gender dysphoria and its treatment is individualized and not completely understood.